2022
DOI: 10.30541/v47i4iipp.963-1008
|View full text |Cite
|
Sign up to set email alerts
|

A Small Open Economy DSGE Model for Pakistan

Abstract: In recent years there has been a growing interest in academics, international policy institutions and central banks1 in developing small-to-medium, even large-scale, open economy macroeconomic models called Dynamic Stochastic General Equilibrium (DSGE) models based on new-Keynesian framework.2 The term DSGE was originally used by Kydland and Prescott (1982) in their seminal contribution on Real Business Cycle (RBC) model. The RBC model is based on neoclassical framewor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 104 publications
1
6
0
Order By: Relevance
“…For instance, Malik and Ahmed (2010) argued that monetary policy in Pakistan is highly accommodative as weights on inflation (0.32) and output (0.19) in monetary policy rule diverge considerably from what have been proposed by Taylor. Nevertheless, Haider and Khan (2008) in context of DSGE model showed that estimated coefficients (1.17 and 0.72) are closer to what conjectured by Taylor rule. The estimated coefficients of present study may be considered as an average with slightly accommodative monetary policy towards inflationary pressures while pursuing growth objective steadfastly.…”
Section: Posterior Distributionsupporting
confidence: 76%
“…For instance, Malik and Ahmed (2010) argued that monetary policy in Pakistan is highly accommodative as weights on inflation (0.32) and output (0.19) in monetary policy rule diverge considerably from what have been proposed by Taylor. Nevertheless, Haider and Khan (2008) in context of DSGE model showed that estimated coefficients (1.17 and 0.72) are closer to what conjectured by Taylor rule. The estimated coefficients of present study may be considered as an average with slightly accommodative monetary policy towards inflationary pressures while pursuing growth objective steadfastly.…”
Section: Posterior Distributionsupporting
confidence: 76%
“…The parameter value of the discount factor () is set in order to obtain the historical mean of the nominal interest rate in the steady state. Following Haider and Khan (2008), the degree of price stickiness () is assumed to be 0.74. This value is consistent with the latest survey-based finding on firms' optimal pricing behavior in Pakistan (see Choudhary, Naeem, Faheem, Hanif, & Pasha, 2011).…”
Section: Bayesian Estimation Resultsmentioning
confidence: 99%
“…In essence, the requirement is to develop a structural model which is free from such criticism and could be useful for policy analysis. Before we start discussing the model it is important to acknowledge the work of Haider andKhan (2008) andAhmed, et al (2012) that have worked on the structure of DSGE model. Both these studies have, however, 'managed' the unavailability of microeconomic parametric values by relying on 'borrowed' values from the countries other than Pakistan.…”
Section: Framework Of Forward Looking Macroeconomic Modelmentioning
confidence: 99%